The artists’ footprint: investigating the distinct contributions of artists engaging the public with climate data - Jacobs, Rachel (2014)
This thesis investigates the distinct contributions of artists who engage the public with climate data, exploring the role of the artists and the value of their contributions by focusing on two studies of artist-led projects. The first investigates how the author’s own artist led collective, Active Ingredient, engaged the public with climate data through a touring interactive artwork. The second study explores the design of an online platform for capturing, authoring and ‘performing’ climate data. This platform was developed and tested by Active Ingredient in collaboration with researchers from the University of Nottingham, and then used by other artists to engage with climate data. The studies reveal how the artistic projects were designed and experienced, through a mixed methods approach requiring the author to shift perspectives in order to investigate her own arts practice alongside the work of other artists in this field. The findings from these studies suggest that the artists adopt a distinctive voice that fosters an emotional engagement with climate data, rather than an informative or persuasive one, that goes beyond ‘environmental knowing’ towards human-scale, embodied, localized and personalized sense making. This research reveals how the artists use the key strategies of performing data, sensory experience and multiple interpretations to provoke these emotional responses. Highlighting the challenges and opportunities of engaging temporal structures and narratives to represent climate data; treating the data as a new material that is embedded into the artworks and embodied in various sensory forms; abstracting and juxtaposing multiple, contrasting and yet related datasets so as to invite comparisons, while opening up spaces between them for interpretation and dialogue. This results in a discussion of the role of technology within the artistic process, how the artists walk a line between authenticity and emotional engagement in their interpretations of climate data and the importance of an ongoing dialogic collaboration between the artists, researchers and climate scientist that support authentic and meaningful engagements with climate data. The research presents rich descriptions of the artists’ strategies for engaging the public with climate data and revealing that artists have a distinctive and powerful role to play in relation to climate change and sustainability; one that Human Computer Interaction (HCI) and Climate Science need to understand as they continue to move into this territory, and where HCI in particular might ultimately learn about how to bring an emotional treatment to many other forms of data.